Characteristics and Quality Assessment of Oleoresin Production through Bore-hole Method in Chir-pine Under Narendranagar Forest Division, Uttarakhand, India - Dharm Singh Meena; Akash; Kamal Bijlwan; B.S. Bhandari (CV. Literasi Indonesia, 2023)
The present study aimed to evaluate the Oleoresin quality in Chir-pine. It was observed that the main compounds of Chir-pine’s Oleoresin were Rosin, α and β-pinene with the highest percentage and are considered products with high commercial value. There was significant variation recorded while testing the quality of Oleoresin in Chir-pine. Oleoresin obtained from the Bore-hole method was found to be pure as compared to the traditional Rill method. The content of Rosin, α - Pinene, β - Pinene, Carene, and Turpentine oil was in good quality in Bore-hole method. It was further observed that in 1 Kg of Oleoresin, about 70.00 -72.20 % of Rosin was obtained in Rill method whereas in Bore-hole method, approximately 74.10 % of Rosin. On the other hand, α – Pinene, β – Pinene was significantly recorded with 20.80 and 03.40 in Bore-hole method as compared to the three year data of Rill method which showed the purity of the Oleoresin in Bore-hole method. So, the present study recorded that best quality of Oleoresin in Bore-hole method as compared to the Rill method.